Short-run money demand - Laurence Ball (The Johns Hopkins University, Department of Economics, 2002)
This paper estimates a long-run demand function for M1, using U.S. data for 1959-1993. The paper interprets deviations from this long-run relation with Goldfeld=s partial adjustment model. A key innovation is the choice of the interest rate in the money demand function. Most previous work uses a short-term market rate, but this paper uses the average return on near monies
Keywords: 330; close substitutes for M1 such as savings accounts and money market mutual funds. This approach yields a predicted path of M1 velocity that closely matches the data. The volatility of velocity after 1980 is explained by volatility in the returns on near monies.; Geldnachfrage; Monetäres Aggregat; Geldumlaufgeschwindigkeit; Schätzung; USA